MODULAR NETWORK SOM (MNSOM): A NEW POWERFUL TOOL IN NEURAL NETWORKS - Muhammad Aziz Muslim (Universitas Ahmad Dahlan, 2009)
In this paper, a new powerful method in artificial neural networks, called modular network SOM (mnSOM) is introduced. mnSOM is a generalization of Self Organizing Maps (SOM) formed by replacing each vector unit of SOM with function module. The modular function could be a multi layer perceptron, a recurrent neural network or even SOM itself. Having this flexibility, mnSOM becomes a new powerful tool in artificial neural network.